Istifadah Tathbiqat Quizizz fi Taqwim Ta’lim Al-Lughah Al-‘Arabiyyah - Muhammad Infithar Al Ahqaf; Ridha Darmawaty (Rumah Jurnal IAIN Bukittinggi, 2021)
Online learning is an alternative in Arabic learning during the COVID-19. To see the progress of students' learning, it is necessary to evaluate online learning by utilizing the mediaone of them is the application Quizizz. This application has adequate features to be used as a means of delivering interesting and fun Arabic learning materials and evaluations. The purpose of this article is to describe the use of the Quizizz application as an online-based evaluation medium for Arabic learning and its possible application in Arabic learning. Data were collected,analyzed, categorized, and concluded through a literature review, both from books and journals related to the evaluation of learning, especially in Arabic using the application Quizizz. This study shows that the evaluation of test-based Arabic learning can be done through the application Quizizz by maximizing the features contained in it, and supported by teacher guidance. Utilization of this application will be maximized if the pro version is implemented to be able to upload sound and video.يعد تعليم اللغة العربية عبر الإنترنت بديلاً للتعليم المباشر أثناء الجائحة. لمعرفة ترقية كفاءة تعلم الطلاب فمن الضروري أن تقييم التعلم عبر الإنترنت باستفادة الوسائط الإفتراضي مثل تطبيقات Quizizz.. تحتوي هذه التطبيقات أدوات متميزة و ملائمة لاستخدامها كوسيلة تقديم المواد التعليمية و تقويم التعليم الممتعة. فالهدف هذا البحث وصف استفادة تطبيقات Quizizz كوسيلة تقويم عبر الإنترنت لتعليم اللغة العربية و إمكانيات التطبيق في مجال تعليم اللغة العربية. قام هذا البحث بمنهج البحث المكتبي بجمع البيانات من المصادر الأولية والثانوية من خلال دراسة أثناء التعليم وأوراق البحوث المتعلقة بتقويم التعليم ، وخاصة باللغة العربية باستخدام تطبيقات Quizizz. فاستنتج هذا البحث إمكانيات تطبيق تقويم تعليم اللغة العربية القائم على الاختبار من خلال تطبيقات Quizizz بأدوات المتميزة الواردة فيها ودعمها تحت إشراف المعلم. وزادت الإستفادة باستخدام إصدار التطبيقات المحترف بأكثر من الآدوات من للتسجيل الأصوات والمقطيع من فيديوهات.